Adult education history in Britain: past, present, and future (part II). (3rd May 2020) - Freeman, Mark
ABSTRACT: This article – the second part of a two-part contribution – offers a number of suggested directions for the historiography of adult education in Britain. It identifies opportunities to address longstanding areas of neglect that have been overshadowed by a focus on the "Great Tradition" of adult education. Although a key theme of recent research is a shift in focus from educational institutions to the study of learners and learning, the article argues that there remains considerable scope for the study of adult education organisations, and identifies four specific areas of opportunity: the examination of the governance of educational institutions, the study of the publications of students and teachers, biographical studies of learners and learning, and geographical and spatial analyses. All these approaches are being productively adopted, and they offer opportunities to draw historians of adult education closer to other developments in modern social, economic and cultural historiography.